Sovereign stress, banking stress, and the monetary transmission mechanism in the Euro area - Oliver Holtemöller; Jan-Christopher Scherer (Asian Development Bank Institute (ADBI), 2018)
In this paper, we investigate to what extent sovereign stress and banking stress have contributed to the increase in the level and in the heterogeneity of non-financial firms' financing costs in the Euro area during the European debt crisis and how both have affected the monetary transmission mechanism. Employing a large firm-level data set containing 2 million observations we are able to identify the effect of government bond yield spreads (sovereign stress) and the share of non-performing loans (banking stress) on firms' financing costs in a panel model by assuming that idiosyncratic shocks to individual firms are uncorrelated with country-specific variables. We find that the two sources of stress have increased firms' financing costs controlling for country and firm-specific factors. Moreover, we estimate both to have significantly impaired the monetary transmission mechanism.
Keywords: E43; E44; E52; 330; Banking stress; firms' financing conditions; government bond yields; interest rate channel; monetary policy transmission; sovereign stress